PROFIL KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DALAM MENYELESAIKAN MASALAH GEOMETRI DITINJAU DARI LEVEL VAN HIELE - Akalili, Imania Aufi (Kadikma, 2020)
Mathematical communication skills are needed to express ideas, messages, and ideas through written or oral. The research subjects were five students of class XII SMAN Ambulu who were categorized in van Hiele level. The results of the data analysis obtained were students with informal deduction had the ability to express mathematical ideas through written or oral, the ability to understand mathematical ideas both orally and in writing and the ability to use terms and notations to present data, and had the ability to present ideas. mathematics in solving or describing models of mathematical problems. Students of analysis have the ability to express mathematical ideas through oral, the ability to understand and evaluate mathematical ideas both orally and in writing, and are able to use mathematical terms and notations in presenting mathematical ideas. Visualization students are able to explain how to describe geometric transformations orally and are able to use notations and terms in presenting data.